2004
DOI: 10.1373/clinchem.2003.026989
|View full text |Cite
|
Sign up to set email alerts
|

Between-Method Variation in Human Chorionic Gonadotropin Test Results

Abstract: Background:Results on sera and calibrators vary 1.4-to 2.3-fold among commercial human chorionic gonadotropin (hCG) assays. The relative contributions of calibrators, standards, hCG charge isoforms, and major structural variants to this variation have not been quantified. Methods: Purified hCG was separated by isoelectric focusing into four fractions with pI ranges of 3-4, 4 -5, 5-6, and 6 -7. These four fractions together with pure hCG, hyperglycosylated hCG, hCG ␤-subunit (hCGb), nicked hCG, and hCGb core fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 19 publications
2
50
0
2
Order By: Relevance
“…The concentration measured, 130 IU/L, corresponds to 0.374 nmol/L hCG, and this corresponds to 3.74 g/L hCG␤cf, i.e., similar to the nominal concentration, 4 g/L. Thus, with the exception of hCG␤cf, no variant is grossly over-or underestimated by any of the assays studied (8 ). This comparison also demonstrates the advantage of using molar concentrations to express values for various forms of hCG (5 ).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The concentration measured, 130 IU/L, corresponds to 0.374 nmol/L hCG, and this corresponds to 3.74 g/L hCG␤cf, i.e., similar to the nominal concentration, 4 g/L. Thus, with the exception of hCG␤cf, no variant is grossly over-or underestimated by any of the assays studied (8 ). This comparison also demonstrates the advantage of using molar concentrations to express values for various forms of hCG (5 ).…”
mentioning
confidence: 51%
“…The authors draw the conclusion that use of impure assay calibrators in combination with variable recognition of hCG subunits and other variants is an important cause of the variation. Analysis of several commercial hCG preparations revealed that most of them contain degraded forms, subunits, and fragments (8 ), and earlier studies have shown that rather crude hCG preparations are used as calibrators (4 ).…”
mentioning
confidence: 99%
“…specific antibody which is O-linked oligosaccharide sensitive, leading to poor detection of hCG-2 [40,41].…”
Section: Volume 3 • Issue 1 •1000222mentioning
confidence: 99%
“…The existence of the six semi-independent molecules was demonstrated by structure studies [9,10,46]. Bold underline poor detection 6 of 9 5 of 9 6 of 9 7 of 9 5 of 9 5 of 9 7 of 9 7 of 9 1 of 9 7 of 9 6 of 7 LH crossreactivity 0.01% 0.01% 0.01% 0.01% 0.32% 0.01% 0.01% 0.01% 0.04% 0.53% 0.01% Table 9: Detection of serum hCG-related molecules by different automated total hCG tests (40,41). ßCTP is ß-subunit C-terminal peptide, RIA is radioimmunoassay.…”
Section: Hcg-1 -Hcg-5 and Hcg Testsmentioning
confidence: 99%
“…The underlying principle of all such tests lies in the immunodetection of proteins that are specifically produced as result of pregnancy. Most often, the human chorionic gonadotropin (hCG) hormone, which is released from the placenta a few days after conception, is employed and detected via immunoassays [2,3]. However, there is at least one field of potential application of molecular pregnancy diagnostics where the detection principle of the currently available tests appears problematic owing to the amount and kind of material available: the forensic field.…”
Section: Forensic Pregnancy Testing: a Special Case In Molecular Diagmentioning
confidence: 99%